Lithium ion battery, preparation method thereof and power utilization device

By using the first coating and multi-layer structural separator of titanium aluminum phosphate in lithium-ion batteries, the problem of insufficient safety performance of lithium-ion battery separator materials is solved, the lithium-ion battery capacity and calendar life are improved, and the lithium-ion battery capacity and calendar life are reduced. Short circuit and thermal runaway risk.

CN119275327AInactive Publication Date: 2025-01-07WUXI QIAODE NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411358903.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery separator materials cannot meet the safety performance requirements of lithium-ion batteries. The oxidation reaction of titanium-aluminum coating with negative electrode active lithium leads to a decrease in the capacity and calendar life of the lithium-ion battery.

Method used

Design a lithium-ion battery, using a first coating of titanium aluminum lithium phosphate, the lithium sheet is arranged between the diaphragm and the negative electrode sheet, and the capacity and calendar life of the lithium-ion battery are improved by melting and aging treatment, using polymers and multi-layer structural diaphragm of heat-resistant material to improve interface adhesion and thermal stability.

Benefits of technology

Through the oxidation reaction of lithium ion in lithium phosphate and lithium ion in lithium sheets, the consumption of negative electrode sheets is reduced, the capacity and calendar life of lithium ion batteries are improved, and the risks of short circuit and thermal runaway are reduced through a multi-layer structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275327A_ABST
    Figure CN119275327A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion battery and a preparation method thereof and a power utilization device, the lithium ion battery comprises a positive plate, a negative plate, a diaphragm arranged between the positive plate and the negative plate and a lithium plate, the lithium plate is arranged between the diaphragm and the negative plate, the diaphragm comprises a base film and a first coating arranged on one side, close to the lithium plate, of the base film, the first coating contains lithium titanium aluminum phosphate, so that the capacity and calendar life of the lithium ion battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery and a preparation method and an electrical device thereof. Background Art

[0002] The diaphragm is located between the positive and negative electrodes of the lithium-ion battery. It is used to prevent the positive and negative electrodes from directly contacting each other and causing a short circuit. At the same time, it allows lithium ions to be transmitted smoothly, prevents electrons from passing through, and ensures the normal charging and discharging process of the battery. Commercial lithium-ion battery diaphragms are mostly PE microporous membranes and PP microporous membranes. However, due to the characteristics of the material itself, the above diaphragms cannot meet the safety performance requirements of lithium-ion batteries. In actual use, the base film of the diaphragm is usually processed, such as coating with lithium aluminum titanium phosphate to improve the safety performance of lithium-ion batteries. However, lithium aluminum titanium phosphate will undergo an oxidation reaction with the active lithium in the negative electrode, resulting in a decrease in the capacity and calendar life of the lithium-ion battery. Summary of the invention

[0003] The present application provides a lithium ion battery and a preparation method thereof and an electrical device to improve the capacity and calendar life of the lithium ion battery.

[0004] In a first aspect of the present application, a lithium-ion battery is provided, which includes a positive electrode sheet, a negative electrode sheet, a separator and a lithium sheet arranged between the positive electrode sheet and the negative electrode sheet, wherein the lithium sheet is arranged between the separator and the negative electrode sheet, and the separator includes a base film and a first coating arranged on a side of the base film adjacent to the lithium sheet, wherein the first coating contains lithium aluminum titanium phosphate.

[0005] In some embodiments, the surface density of the lithium sheet is 0.0025 g / cm 2 ~0.005g / cm 2 .

[0006] In some embodiments, the thickness of the lithium sheet is 0.5 μm to 3 μm.

[0007] In some embodiments, the first coating has a thickness of 1 μm to 5 μm.

[0008] In some embodiments, the mass fraction of lithium aluminum titanium phosphate in the first coating layer is 90% to 96%.

[0009] In some embodiments, the diaphragm further comprises a second coating, wherein the second coating comprises a polymer, wherein the polymer comprises one or more of polyvinylidene fluoride and polymethyl methacrylate, and the second coating has at least one of the following features (1) to (3):

[0010] (1) The second coating layer is disposed on a side of the first coating layer away from the base film;

[0011] (2) the second coating layer is disposed on a side of the base film away from the first coating layer;

[0012] (3) The surface density of the polymer in the second coating is 0.5 g / m 2 ~0.8g / m 2 .

[0013] In some embodiments, the diaphragm further comprises a third coating, the third coating being disposed on at least one surface of the base film, the third coating comprising a heat-resistant material, and the heat-resistant material having at least one of the following characteristics (1) to (2):

[0014] (1) The heat-resistant material includes one or more of alumina, aluminum oxyhydroxide and boehmite;

[0015] (2) The surface density of the heat-resistant material in the third coating is 2 g / m 3 ~4.5g / m 3 .

[0016] In some embodiments, the material of the base film includes a polyolefin compound, and the polyolefin compound includes one or more of polyethylene and polypropylene.

[0017] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, a tin-based material, and lithium titanate.

[0018] In a second aspect of the present application, a method for preparing a lithium ion battery is provided, comprising the following steps:

[0019] A semi-finished battery comprising a positive electrode sheet, a separator, a lithium sheet and a negative electrode sheet is provided; the separator and the lithium sheet are arranged between the positive electrode sheet and the negative electrode sheet, the lithium sheet is arranged between the separator and the negative electrode sheet, the separator comprises a base film and a first coating layer arranged on a side of the base film adjacent to the lithium sheet, the first coating layer comprises lithium aluminum titanium phosphate;

[0020] The battery semi-finished product is subjected to formation treatment and aging treatment in sequence to prepare the lithium-ion battery.

[0021] In some embodiments, the process conditions of the chemical formation treatment include: a chemical formation temperature of 50° C. to 80° C., and a chemical formation pressure of 0.5 MPa to 1.5 MPa.

[0022] In some embodiments, the process conditions of the aging treatment include: an aging temperature of 50° C. to 80° C., and an aging time of 12 h to 36 h.

[0023] In some embodiments, after the steps of sequentially performing formation treatment and aging treatment on the semi-finished battery product, the step further includes: performing capacity division treatment on the semi-finished battery product obtained by the aging treatment; the capacity division treatment includes: performing 1 to 5 cycle charge and discharge treatments on the semi-finished battery product obtained by the aging treatment at a current of 0.1C to 1C within a voltage range of 1V to 3.65V.

[0024] In some embodiments, the method for preparing the semi-finished battery product comprises the following steps:

[0025] Rolling the lithium sheet onto one side of the negative electrode sheet to obtain a composite electrode sheet;

[0026] Winding or stacking the positive electrode sheet, the separator and the composite electrode sheet to form an electrode assembly;

[0027] The electrode assembly is placed in the outer packaging of the battery, and the electrolyte is injected and packaged to obtain the semi-finished battery.

[0028] The third aspect of the present application provides an electrical device, comprising at least one of the lithium-ion battery described in the first aspect of the present application and the lithium-ion battery prepared by the preparation method described in the second aspect of the present application.

[0029] Compared with traditional technologies, the above lithium-ion batteries have at least the following advantages:

[0030] The lithium sheet in the above-mentioned lithium-ion battery can provide lithium ions, and the first coating layer containing lithium aluminum titanium phosphate is arranged between the base film and the lithium sheet, so that the lithium aluminum titanium phosphate can undergo an oxidation reaction with the lithium ions in the lithium sheet, reducing the consumption of lithium aluminum titanium phosphate for lithium ions in the negative electrode sheet, thereby improving the capacity and calendar life of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] FIG1 is a schematic diagram of a positive electrode sheet, a negative electrode sheet, a separator and a lithium sheet in one embodiment of the present application.

[0032] FIG. 2 is a schematic structural diagram of a diaphragm according to an embodiment of the present application.

[0033] FIG3 is a schematic structural diagram of a diaphragm according to another embodiment of the present application.

[0034] FIG. 4 is a schematic structural diagram of a diaphragm according to another embodiment of the present application.

[0035] FIG. 5 is a schematic structural diagram of a diaphragm according to another embodiment of the present application.

[0036] FIG. 6 is a schematic diagram of the structure of the diaphragm of Example 1 of the present application.

[0037] FIG. 7 is a schematic diagram of the structure of the diaphragm of Example 5 of the present application.

[0038] FIG8 is an X-ray diffraction diagram of lithium aluminum titanium phosphate, base film and diaphragm used in Example 5 of the present application.

[0039] Figure 9 is a picture of the diaphragm, positive electrode sheet and negative electrode sheet after hot pressing of Examples 4 and 5 of the present application; (a) in Figure 9 is a picture of the diaphragm, positive electrode sheet and negative electrode sheet after hot pressing of Example 4; (b) in Figure 9 is a picture of the diaphragm, positive electrode sheet and negative electrode sheet after hot pressing of Example 5.

[0040] Description of reference numerals:

[0041] 1 positive electrode sheet; 2; negative electrode sheet; 3 separator; 31 base film; 32 first coating layer; 33 second coating layer; 34 third coating layer; 4 lithium sheet. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0043] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0044] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0045] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0046] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0047] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in this application and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more related listed items. The term "multiple" in this application means at least two, such as two, three, etc., unless otherwise clearly and specifically limited.

[0048] One embodiment of the present application provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator arranged between the positive electrode sheet and the negative electrode sheet, and a lithium sheet, the lithium sheet is arranged between the separator and the negative electrode sheet, the separator includes a base film and a first coating arranged on a side of the base film adjacent to the lithium sheet, and the first coating contains lithium aluminum titanium phosphate.

[0049] The lithium sheet in the above lithium-ion battery can provide lithium ions, and the first coating layer containing lithium aluminum titanium phosphate (LATP) is arranged between the base film and the lithium sheet, so that the lithium aluminum titanium phosphate can react with the lithium ions in the lithium sheet to reduce the consumption of lithium aluminum titanium phosphate for lithium ions in the negative electrode sheet, thereby improving the capacity and calendar life of the lithium-ion battery. The chemical formula of lithium aluminum titanium phosphate is Li 1+x Al x Ti 2-x (PO4)3, where 0.3≤x≤0.5.

[0050] FIG1 is a schematic diagram of a positive electrode sheet, a negative electrode sheet, a separator and a lithium sheet in an embodiment of the present application. In some embodiments, in conjunction with FIG1, a lithium-ion battery includes a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 disposed between the positive electrode sheet 1 and the negative electrode sheet 2, and a lithium sheet 4, wherein the lithium sheet 4 is disposed between the separator 3 and the negative electrode sheet 2, and the separator 3 includes a base film 31 and a first coating 32 disposed on a side of the base film 31 adjacent to the lithium sheet 4, wherein the first coating 32 contains lithium aluminum titanium phosphate.

[0051] In some embodiments, the surface density of the lithium sheet is 0.0025 g / cm 2 ~0.005g / cm 2 Controlling the surface density of the lithium sheet to the above range is conducive to the full reaction of lithium ions provided by the lithium sheet with lithium aluminum titanium phosphate, thereby being more conducive to improving the capacity and calendar life of the lithium ion battery. Specifically, the surface density of the lithium sheet includes but is not limited to: 0.0025g / cm 2 , 0.003g / cm 2 , 0.0035g / cm2 、0.004g / cm 2 , 0.0045g / cm 2 , 0.005g / cm 2 Or a range between any two of the foregoing.

[0052] In some embodiments, the thickness of the lithium sheet is 0.5 μm to 3 μm. Controlling the thickness of the lithium sheet to the above range is conducive to the full reaction of lithium ions provided by the lithium sheet with lithium aluminum titanium phosphate, thereby being more conducive to improving the capacity and calendar life of the lithium ion battery. Specifically, the thickness of the lithium sheet includes but is not limited to: 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or a range between any two of the foregoing.

[0053] In some embodiments, the thickness of the first coating layer is 1 μm to 5 μm. Specifically, the thickness of the first coating layer includes but is not limited to: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or a range between any two of the foregoing.

[0054] In some embodiments, the mass fraction of lithium aluminum titanium phosphate in the first coating is 90% to 96%. Controlling the mass fraction of lithium aluminum titanium phosphate in the first coating to be within the above range is beneficial to reducing the risk of thermal runaway of lithium-ion batteries. Specifically, the mass fraction of lithium aluminum titanium phosphate in the first coating includes, but is not limited to, 90%, 91%, 92%, 93%, 94%, 95%, 96%, or a range between any two of the foregoing.

[0055] In some embodiments, the separator further comprises a second coating, the second coating comprises a polymer, and the polymer comprises one or more of polyvinylidene fluoride and polymethyl methacrylate. The above polymer has a certain adhesiveness, which can improve the interfacial adhesion, making it relatively easy to place the electrode assembly including the positive electrode sheet, the separator and the negative electrode sheet in the battery outer packaging, which can reduce the risk of short circuit of the lithium-ion battery.

[0056] In some embodiments, the second coating layer is disposed on a side of the first coating layer that is away from the base film.

[0057] FIG2 is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application. In some embodiments, in conjunction with FIG2 , the diaphragm 3 further includes a second coating 33 , and the second coating 33 is disposed on a side of the first coating 32 away from the base film 31 .

[0058] In some embodiments, the second coating is disposed on a side of the base film away from the first coating.

[0059] FIG3 is a schematic diagram of the structure of a diaphragm according to another embodiment of the present application. In other embodiments, in conjunction with FIG3 , the diaphragm 3 further includes a second coating 33 , and the second coating 33 is disposed on a side of the base film 31 away from the first coating 32 .

[0060] FIG4 is a schematic diagram of the structure of another embodiment of the diaphragm of the present application. In other embodiments, in conjunction with FIG4 , the diaphragm 3 further includes a second coating 33 , which is disposed on a side of the first coating 32 away from the base film 31 , and on a side of the base film 31 away from the first coating 32 .

[0061] In some embodiments, the polymer in the second coating has an area density of 0.5 g / m 2 ~0.8g / m 2 Specifically, the surface density of the polymer in the second coating includes but is not limited to: 0.5 g / m 2 , 0.55g / m 2 , 0.6g / m 2 , 0.65g / m 2 , 0.7g / m 2 , 0.75g / m 2 , 0.8g / m 2 Or a range between any two of the foregoing.

[0062] It should be noted that the second coating is arranged on the side of the first coating away from the base film, or the second coating is arranged on the side of the base film away from the first coating, or the second coating is arranged on the side of the first coating away from the base film and on the side of the base film away from the first coating. The second coating can reduce the risk of short circuit of the lithium-ion battery. Furthermore, the second coating is arranged on the side of the first coating away from the base film, which can enhance the interfacial bonding between the first coating and the lithium sheet, and further reduce the risk of short circuit of the lithium-ion battery.

[0063] In some embodiments, the diaphragm further includes a third coating, which is disposed on at least one surface of the base film and contains a heat-resistant material. This design can improve the thermal stability of the diaphragm and further reduce the risk of thermal runaway of the lithium-ion battery.

[0064] As a non-limiting example, the third coating layer is disposed on a single-side surface or on both-side surfaces of the base film.

[0065] FIG5 is a schematic diagram of the structure of a diaphragm according to another embodiment of the present application. In some other embodiments, the diaphragm 3 further includes a third coating 34 , and the third coating 34 is disposed on both sides of the base film 31 .

[0066] In some embodiments, the refractory material includes one or more of alumina, aluminum oxyhydroxide, and boehmite.

[0067] In some embodiments, the surface density of the heat-resistant material in the third coating layer is 2 g / m 3 ~4.5g / m 3Specifically, the bulk density of heat-resistant materials includes but is not limited to: 2g / m 3 , 2.5g / m 3 , 3g / m 3 3.5g / m 3 , 4g / m 3 4.5g / m 3 Or a range between any two of the foregoing. Optionally, the thickness of the third coating layer is 3 μm.

[0068] In some embodiments, the material of the base film includes a polyolefin compound, and the polyolefin compound includes one or more of polyethylene and polypropylene.

[0069] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, a tin-based material, and lithium titanate.

[0070] In some embodiments, the carbon-based material includes at least one of graphite, hard carbon, and soft carbon.

[0071] Another embodiment of the present application provides a method for preparing a lithium ion battery, comprising the following steps:

[0072] A semi-finished battery comprising a positive electrode sheet, a separator, a lithium sheet and a negative electrode sheet is provided; the separator and the lithium sheet are arranged between the positive electrode sheet and the negative electrode sheet, the lithium sheet is arranged between the separator and the negative electrode sheet, the separator comprises a base film and a first coating arranged on a side of the base film adjacent to the lithium sheet, and the first coating comprises lithium aluminum titanium phosphate;

[0073] The semi-finished battery product is subjected to formation treatment and aging treatment in sequence to prepare a lithium-ion battery.

[0074] The lithium sheet in the lithium-ion battery prepared by the above preparation method can provide lithium ions. The first coating layer containing lithium aluminum titanium phosphate (LATP) is arranged between the base film and the lithium sheet, so that the lithium aluminum titanium phosphate can undergo an oxidation reaction with the lithium ions in the lithium sheet, reducing the consumption of lithium aluminum titanium phosphate for lithium ions in the negative electrode sheet, thereby improving the capacity and calendar life of the lithium-ion battery.

[0075] In some embodiments, the process conditions of the formation treatment include: a formation temperature of 50°C to 80°C, and a formation pressure of 0.5MPa to 1.5MPa. Controlling the process conditions of the formation treatment to the above range can promote the reaction of lithium aluminum titanium phosphate with lithium ions in the lithium sheet, further reduce the consumption of lithium aluminum titanium phosphate for lithium ions in the negative electrode sheet, thereby further improving the capacity and calendar life of the lithium ion battery. Specifically, the formation temperature includes but is not limited to: 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range between any two of the foregoing, and the formation pressure includes but is not limited to: 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1MPa, 1.1MPa, 1.2MPa, 1.3MPa, 1.4MPa, 1.5MPa or a range between any two of the foregoing.

[0076] In some embodiments, the process conditions of the aging treatment include: an aging temperature of 50° C. to 80° C., and an aging time of 12 h to 36 h. Controlling the process conditions of the aging treatment within the above range can promote the reaction between lithium titanium aluminum phosphate and lithium ions in the lithium sheet, further reduce the consumption of lithium titanium aluminum phosphate for lithium ions in the negative electrode sheet, and thus further improve the capacity and calendar life of the lithium-ion battery.

[0077] In some embodiments, after the steps of sequentially performing formation treatment and aging treatment on the semi-finished battery, the step of performing capacity separation treatment on the semi-finished battery obtained by the aging treatment comprises: performing 1 to 5 cycles of charge and discharge treatment on the semi-finished battery obtained by the aging treatment at a current of 0.1C to 1C within a voltage range of 1V to 3.65V. Through the above-mentioned capacity separation treatment, the lithium aluminum titanium phosphate can fully react with the lithium ions in the lithium sheet, which is more conducive to improving the capacity and calendar life of the lithium ion battery.

[0078] In some embodiments, the method for preparing a semi-finished battery comprises the following steps:

[0079] Rolling the lithium sheet onto one side of the negative electrode sheet to obtain a composite electrode sheet;

[0080] Winding or stacking the positive electrode sheet, the separator and the composite electrode sheet to form an electrode assembly;

[0081] The electrode assembly is placed in the battery outer packaging, the electrolyte is injected, and the battery is packaged to obtain a semi-finished battery.

[0082] In some embodiments, a first coating layer containing lithium aluminum titanium phosphate is formed on one side of the base film by coating. For example, a slurry containing lithium aluminum titanium phosphate and styrene-butadiene rubber can be coated on one side of the base film and dried to form the first coating layer containing lithium aluminum titanium phosphate.

[0083] In some embodiments, the second coating layer comprising a polymer is formed by spraying.

[0084] In some embodiments, a third coating layer comprising a heat-resistant material is formed on at least one surface of the base film by coating. For example, a slurry comprising a heat-resistant material and styrene-butadiene rubber may be coated on at least one surface of the base film and dried to form the third coating layer comprising a heat-resistant material.

[0085] Another embodiment of the present application provides an electric device, including at least one of the lithium ion battery described above and the lithium ion battery prepared by the preparation method described above. The lithium ion battery can be used as a power source for the electric device or as an energy storage unit for the electric device. The electric device can include a mobile phone, a laptop computer, an electric car, an electric bicycle, etc., but is not limited thereto.

[0086] In order to further illustrate the present application, the technical scheme of the present application is described in detail below in conjunction with specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0087] Example 1

[0088] The preparation method of a lithium-ion battery comprises the following steps:

[0089] (1) A 9 μm thick PE film was used as a base film. A slurry containing lithium aluminum titanium phosphate and styrene butadiene rubber (wherein the mass ratio of lithium aluminum titanium phosphate to styrene butadiene rubber was 95:5) was coated on the surface of one side of the base film, and a lithium aluminum titanium phosphate (LATP) layer (first coating layer) with a thickness of 1 μm was formed after drying. A slurry containing Al2O3 and styrene butadiene rubber (wherein the mass ratio of Al2O3 to styrene butadiene rubber was 95:5) was coated on the surface of the other side of the base film, and a 0.6 g / m 2 The second coating is formed by adding polyvinylidene fluoride (PVDF) to obtain a diaphragm, the structure of which is shown in FIG6 . The surface density of the PVDF in the second coating is about 0.6 g / m 2 The thickness of the third coating is 3 μm, and the surface density of Al2O3 is about 3.5 g / m 2 ;

[0090] (2) adding positive electrode active material lithium iron phosphate, conductive agent acetylene black, carbon nanotubes, and binder PVDF in a mass ratio of 96:1:1:2 to N-methylpyrrolidone, stirring and mixing them in a dry environment filled with nitrogen until they are evenly mixed, coating them on carbon-coated Al foil, drying them, and cold pressing them to obtain a positive electrode sheet;

[0091] (3) The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener carbon methyl cellulose sodium (CMC-Na) were fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:2:1:1, and then coated on a Cu foil, dried, and cold pressed to obtain a negative electrode sheet; in a dry environment filled with nitrogen, a Cu foil with a surface density of 0.0037 g / cm 2 , rolling a lithium sheet with a thickness of 2 μm on one side of the negative electrode sheet to obtain a Li / graphite composite electrode sheet;

[0092] (4) dissolving lithium salts LiPF6 and LiTFSI and electrolyte additive vinylene carbonate (VC) in a solvent to prepare an electrolyte; wherein the volume ratio of the solvent is EC:EMC:DMC=3:5:2, the mass ratio of LiPF6 to LiTFSI is 5:1, and the mass proportion of the electrolyte additive in the electrolyte is 3%;

[0093] (5) stacking the positive electrode sheet, the separator, and the Li / graphite composite electrode sheet in order, so that the separator is between the positive electrode sheet and the Li / graphite composite electrode sheet to play an isolating role, and the LATP layer (first coating) of the separator faces the negative electrode sheet, and winding to obtain an electrode assembly; placing the electrode assembly in a battery outer packaging, injecting electrolyte, encapsulating, and shelving to obtain a semi-finished battery;

[0094] (6) The semi-finished battery product is subjected to formation treatment, aging treatment, secondary packaging treatment and capacity division treatment in sequence to obtain a soft-pack lithium-ion battery; the formation temperature is 50° C., the formation pressure is 1 MPa, the aging temperature is 50° C., the aging time is 24 h, and the capacity division treatment is to perform three charge and discharge cycles on the semi-finished battery product obtained by secondary packaging at a current of 0.33 C within a voltage range of 2.5 V to 3.65 V.

[0095] Example 2

[0096] The preparation method is similar to that of Example 1, except that in step (6), the formation temperature and the aging temperature are both 60°C.

[0097] Example 3

[0098] The preparation method is similar to that of Example 1, except that in step (6), the formation temperature and the aging temperature are both 70°C.

[0099] Example 4

[0100] The preparation method is similar to that of Example 1, except that in step (6), the capacity division treatment is to perform three charge and discharge cycles on the semi-finished battery obtained by secondary packaging at a current of 0.33C within a voltage range of 1V to 3.65V.

[0101] Example 5

[0102] The preparation method is similar to that of Example 4, except that in step (1), 0.6 g / m 2 of Al2O3 is sprayed on the surface of the Al2O3 layer (third coating) away from the LATP layer (first coating) and on the surface of the LATP layer (first coating) away from the base film. 2 The second coating layer is formed by polyvinylidene fluoride (PVDF), and the surface density of PVDF in the second coating layer is about 0.6 g / m 2 The structural schematic diagram of the obtained diaphragm is shown in Figure 7.

[0103] Example 6

[0104] The preparation method is similar to that of Example 1, except that in step (6), the formation temperature and the aging temperature are both 45°C.

[0105] Comparative Example 1

[0106] The preparation method is similar to that of Example 1, except that in step (1), the surface of one side of the base film is not coated with a slurry comprising lithium aluminum titanium phosphate and styrene-butadiene rubber; that is, the separator does not contain a LATP layer (first coating).

[0107] Comparative Example 2

[0108] The preparation method is similar to that of Example 1, except that in step (5), the Li / graphite composite electrode sheet is replaced with the negative electrode sheet prepared in step (3); that is, the lithium-ion battery does not contain a lithium sheet.

[0109] Comparative Example 3

[0110] The preparation method is similar to that of Example 1, except that in step (1), the LATP layer is replaced by a PVDF layer; that is, PVDF is coated on the surface of one side of the base film to form a PVDF layer with a thickness of 1 μm.

[0111] Comparative Example 4

[0112] The preparation method is similar to that of Example 1, except that in step (5), the Li / graphite composite electrode sheet is replaced with the negative electrode sheet prepared in step (3); that is, the lithium-ion battery does not contain a lithium sheet.

[0113] Comparative Example 5

[0114] The preparation method is similar to that of Comparative Example 4, except that in step (6), the capacity division treatment is to perform one charge and discharge cycle on the semi-finished battery obtained by secondary packaging at a current of 0.33C within a voltage range of 1V to 3.65V.

[0115] Comparative Example 6

[0116] The preparation method is similar to that of Comparative Example 4, except that in step (6), the capacity division treatment is to perform two charge and discharge cycles on the semi-finished battery obtained by secondary packaging at a current of 0.33C within a voltage range of 1V~3.65V.

[0117] Comparative Example 7

[0118] The preparation method is similar to that of Comparative Example 4, except that in step (6), the capacity division treatment is to perform three charge and discharge cycles on the semi-finished battery obtained by secondary packaging at a current of 0.33C within a voltage range of 1V to 3.65V.

[0119] Figure 8 shows the X-ray diffraction patterns of lithium aluminum titanium phosphate (LATP), the base film and the separator used in Example 5. As can be seen from Figure 8, Example 5 successfully coated LATP on the base film.

[0120] Figure 9 shows the pictures of the separator, positive electrode sheet and negative electrode sheet after hot pressing of Example 4 and Example 5. Compared with Example 4, Example 5 adds a second coating formed by spraying PVDF on the surface of the LATP layer away from the base film. As shown in Figure 9, the separator, positive electrode sheet and negative electrode sheet of Example 5 are more compact after hot pressing, which can reduce the difficulty of loading into the battery outer packaging, and the separator can be located between the positive electrode sheet and the negative electrode sheet, effectively reducing the risk of short circuit of the lithium-ion battery.

[0121] Test Case

[0122] (1) First coulombic efficiency and capacity test

[0123] At 45°C and pressurized (pressure is 1MPa), the lithium-ion battery is charged at a constant current rate of 0.1C to a voltage of 3.2V, and the total charge capacity at this time is recorded as C1; after the lithium-ion battery is aged at high temperature for 24 hours according to the aging temperature in Table 1, the battery is charged at a constant current and voltage rate of 0.33C to a voltage of 3.65V at 25°C and no pressure, and the cut-off current is 0.05C, and the charge capacity at this time is recorded as C2. After charging, let it stand for 15 minutes, discharge it at a constant current of 0.33C to 2.5V, and record the discharge capacity as DC1, which is the measured capacity. The first coulomb efficiency (%) = DC1 / (C1+C2)*100%.

[0124] (2) Storage remaining capacity and recovery capacity test

[0125] At room temperature (25±2℃), the lithium-ion battery was charged and discharged at 1C / 1C (discharge capacity was recorded as DC2), and then the above battery was charged to 3.65V at 1C constant current and constant voltage to obtain a fully charged lithium-ion battery; the above fully charged lithium-ion battery was placed in a 60℃ high temperature box for 15 days, and discharged at 1C at room temperature (discharge capacity was recorded as DC3); and then charged and discharged at 1C / 1C at room temperature (discharge capacity was recorded as DC4). The upper limit voltage of the above charging is 3.65V, and the lower limit voltage of the discharge is 2.5V.

[0126] Storage at 60℃ for 15 days. Capacity retention rate (%) = DC3 / DC2×100%;

[0127] Capacity recovery rate (%) after 15 days of storage at 60°C = DC4 / DC2×100%.

[0128] (3) Acupuncture test

[0129] Select three batteries from the same group and conduct a needle puncture test in accordance with GB / T 31485-2015 "Safety Requirements and Test Methods for Power Batteries for Electric Vehicles". The diameter of the steel needle is 5mm and the speed is 25mm / s. Observe whether the battery smokes or catches fire. If none of the three batteries in the same group smokes or catches fire during the needle puncture test, it means that the battery has passed the needle puncture test.

[0130] Table 1

[0131]

[0132] As shown in Table 1, compared with Comparative Example 2 and Comparative Examples 4 to 7, the first coulombic efficiency, capacity, capacity retention rate after 15 days of storage at 60°C and capacity recovery rate after 15 days of storage at 60°C of the batteries of Examples 1 to 6 are relatively high, indicating that the lithium sheet and the separator containing lithium aluminum titanium phosphate provided in the batteries of Examples 1 to 6 can be used together to improve the capacity and calendar life of the battery. In addition, the batteries of Examples 1 to 6 can all pass the puncture test, while the batteries of Comparative Examples 1 and 3 fail the puncture test. This is because the first coating of the separators of Comparative Examples 1 and 3 does not contain lithium aluminum titanium phosphate, and the thermal runaway risk of the battery is relatively high, resulting in the safety performance of the batteries of Comparative Examples 1 and 3 being far inferior to that of the batteries of Examples 1 to 6.

[0133] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0134] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator arranged between the positive electrode sheet and the negative electrode sheet, and a lithium sheet, wherein the lithium sheet is arranged between the separator and the negative electrode sheet, the separator comprises a base film and a first coating arranged on a side of the base film adjacent to the lithium sheet, wherein the first coating contains lithium aluminum titanium phosphate.

2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery has at least one of the following characteristics (1) to (4): (1) The surface density of the lithium sheet is 0.0025 g / cm 2 ~0.005g / cm 2 ; (2) The thickness of the lithium sheet is 0.5 μm to 3 μm; (3) The thickness of the first coating is 1 μm to 5 μm; (4) The mass fraction of lithium aluminum titanium phosphate in the first coating is 90% to 96%.

3. The lithium-ion battery according to claim 1, characterized in that The diaphragm further includes a second coating, the second coating includes a polymer, the polymer includes one or more of polyvinylidene fluoride and polymethyl methacrylate, and the second coating has at least one of the following characteristics (1) to (3): (1) The second coating layer is disposed on a side of the first coating layer away from the base film; (2) the second coating layer is disposed on a side of the base film away from the first coating layer; (3) The surface density of the polymer in the second coating is 0.5 g / m 2 ~0.8g / m 2 .

4. The lithium ion battery according to any one of claims 1 to 3, characterized in that The diaphragm further includes a third coating layer, which is disposed on at least one surface of the base film. The third coating layer includes a heat-resistant material, and the heat-resistant material has at least one of the following characteristics (1) to (2): (1) The heat-resistant material includes one or more of alumina, aluminum oxyhydroxide and boehmite; (2) The surface density of the heat-resistant material in the third coating is 2 g / m 2 ~4.5g / m 2 .

5. The lithium ion battery according to any one of claims 1 to 3, characterized in that The lithium-ion battery has at least one of the following characteristics (1) to (2): (1) The material of the base film includes a polyolefin compound, and the polyolefin compound includes one or more of polyethylene and polypropylene; (2) The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material, a silicon-based material, a tin-based material and lithium titanate.

6. A method for preparing a lithium ion battery, characterized in that: The steps include: A semi-finished battery comprising a positive electrode sheet, a separator, a lithium sheet and a negative electrode sheet is provided; the separator and the lithium sheet are arranged between the positive electrode sheet and the negative electrode sheet, the lithium sheet is arranged between the separator and the negative electrode sheet, the separator comprises a base film and a first coating layer arranged on a side of the base film adjacent to the lithium sheet, the first coating layer comprises lithium aluminum titanium phosphate; The battery semi-finished product is subjected to formation treatment and aging treatment in sequence to prepare the lithium-ion battery.

7. The preparation method according to claim 6, characterized in that: The preparation method meets at least one of the following conditions (1) to (2): (1) The process conditions of the chemical formation treatment include: a chemical formation temperature of 50° C. to 80° C. and a chemical formation pressure of 0.5 MPa to 1.5 MPa; (2) The process conditions of the aging treatment include: an aging temperature of 50°C to 80°C and an aging time of 12h to 36h.

8. The preparation method according to claim 6 or 7, characterized in that: After the steps of sequentially performing formation treatment and aging treatment on the semi-finished battery product, the method further includes: performing capacity division treatment on the semi-finished battery product obtained by the aging treatment; the capacity division treatment includes: performing 1 to 5 cycle charge and discharge treatments on the semi-finished battery product obtained by the aging treatment at a current of 0.1C to 1C within a voltage range of 1V to 3.65V.

9. The preparation method according to claim 6 or 7, characterized in that: The method for preparing the semi-finished battery product comprises the following steps: Rolling the lithium sheet onto one side of the negative electrode sheet to obtain a composite electrode sheet; Winding or stacking the positive electrode sheet, the separator and the composite electrode sheet to form an electrode assembly; The electrode assembly is placed in the outer packaging of the battery, and the electrolyte is injected and packaged to obtain the semi-finished battery.

10. An electrical device, characterized in that: The invention comprises at least one of the lithium ion battery according to any one of claims 1 to 5 and the lithium ion battery prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Lithium ion battery, composite diaphragm and preparation method thereof

    CN120016090A